Perancangan Antarmuka Pengguna Sistem Antrian Aduan IT Support sebagai Analisis Tren Keluhan Pengguna - I Gusti Ngurah Ajung Bagus Ogastya Avatara Rayna; Kadek Surya Adi Saputra (Pusat Riset dan Inovasi Nasional, 2026)
Advances in information technology within the banking sector require internal systems capable of supporting operations efficiently and in a structured manner. IT Support services are a crucial component in addressing technical issues faced by employees. However, in practice, the process of submitting and managing complaints at Bank BTN’s Denpasar Branch has not been optimally managed, leading to delays in resolution, a lack of transparency regarding status updates, and difficulties in tracking complaint histories. This study aims to design a user interface for an IT Support complaint queue system that aligns with user needs. The method employed is User-Centered Design (UCD), comprising the stages of needs identification, design development, and evaluation using the System Usability Scale (SUS). The research results consist of a prototype interface featuring complaint submission, status monitoring, and complaint management by IT Support. Testing results showed an average SUS score of 70.8 for internal respondents and 75.17 for general respondents, indicating that the system has a good level of usability and is acceptable to users. Thus, this design is expected to serve as a reference in the development of a more effective and structured IT Support queue system in the banking environment.